2015
DOI: 10.1007/s00467-015-3115-5
|View full text |Cite
|
Sign up to set email alerts
|

Renal formulas pretreated with medications alters the nutrient profile

Abstract: Background Pretreating renal formulas with medications to lower the potassium and phosphorus content is common in clinical practice; however, the effect of this treatment on other nutrients is relatively unstudied. We examine whether nutrient composition is affected by pretreating renal formulas with sodium polystyrene sulfonate (SPS) suspension and sevelamer carbonate. Methods Fixed medication doses and treatment times were utilized to determine changes in the nutrient composition of Suplena® and Similac® P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 21 publications
(69 reference statements)
1
22
0
Order By: Relevance
“…Several prior in vitro studies evaluating pretreatment of EN with SPS have shown significant reductions in the formula content of potassium (6–89%) and concomitant increases in the sodium content (86–527%) [ 3–9 ]. Most in vitro studies have also demonstrated reductions in formula calcium content (8–84%); however, conflicting information is available regarding the effect of pretreatment of formula on magnesium and phosphorus content [ 3 , 5 , 6 , 9 ]. Discrepancies reported in the in vitro studies are likely due to variations in preparation techniques and dosing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several prior in vitro studies evaluating pretreatment of EN with SPS have shown significant reductions in the formula content of potassium (6–89%) and concomitant increases in the sodium content (86–527%) [ 3–9 ]. Most in vitro studies have also demonstrated reductions in formula calcium content (8–84%); however, conflicting information is available regarding the effect of pretreatment of formula on magnesium and phosphorus content [ 3 , 5 , 6 , 9 ]. Discrepancies reported in the in vitro studies are likely due to variations in preparation techniques and dosing.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, they also reported a significant reduction in serum calcium levels (10.7 versus 10.0 mg/dL; P = 0.014) with no significant change in serum sodium or magnesium levels. The authors denied any clinically noticeable side effects but did note that, in their experience, many infants require calcium and magnesium supplementation when receiving SPS-treated EN [ 9 ]. Although, the five patients described by Bunchman et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modulars, discussed below, can increase caloric density if needed. The clinician should do their best to work breastmilk into the feeding regimen, not wasting any of the typically hard-earned liquid, if the mother is willing and able to provide any, even for the short-term (36). …”
Section: Fitting Enteral Products To Patient Needsmentioning
confidence: 99%
“…This make it difficult to know what nutrients the individual is receiving and whether micronutrient inadequacy or excess may be occurring. Additionally, use of a liquid suspension greatly increases aluminum content of the formula (36). Thus, if this product is used, the powdered version should be chosen.…”
Section: Unique Adjustments To Enteral Feedingsmentioning
confidence: 99%